Effects of all-out sprint interval training under hyperoxia on exercise performance - Kon, M.; Nakagaki, K.; Ebi, Y. (Physiological Reports, 2019)
All-out sprint interval training (SIT) is speculated to be an effective and time-efficient training regimen to improve the performance of aerobic and anaerobic exercises. SIT under hypoxia causes greater improvements in anaerobic exercise performance compared with that under normoxia. The change in oxygen concentration may affect SIT-induced performance adaptations. In this study, we aimed to investigate the effects of all-out SIT under hyperoxia on the performance of aerobic and anaerobic exercises. Eighteen college male athletes were randomly assigned to either the normoxic sprint interval training (NST, n = 9) or hyperoxic (60% oxygen) sprint interval training (HST, n = 9) group and performed 3-week SIT (six sessions) consisting of four to six 30-sec all-out cycling sessions with 4-min passive rest. They performed maximal graded exercise, submaximal exercise, 90-sec maximal exercise, and acute SIT tests on a cycle ergometer before and after the 3-week intervention to evaluate the performance of aerobic and anaerobic exercises. Maximal oxygen uptake significantly improved in both groups. However, blood lactate curve during submaximal exercise test significantly improved only in the HST group. The accumulated oxygen deficit (AOD) during 90-sec maximal exercise test significantly increased only in the NST group. The average values of mean power outputs over four bouts during the acute SIT test significantly improved only in the NST group. These findings suggest that all-out SIT might induce greater improvement in aerobic exercise performance (blood lactate curve) but impair SIT-induced enhancements in anaerobic exercise performance (AOD and mean power output).